50 Years of ASEAN: Cooperation in Southeast Asia - Ridha Amalia (Lampung Center for Global Studies (LCGS), 2023)
The Association of Southeast Asian Nations (ASEAN) has earned its place as an important player in international relation especially in the Asia Pacific region. ASEAN has dramatically changed in 50 years, thus it is important to discuss the progress of cooperation established among member states. The aim of this essay is to discuss security, economy and environment cooperation between member states. By the end of the essay, we will have an understanding towards what extend the cooperation established in ASEAN, in its half-century anniversary.